2018
DOI: 10.1016/j.ijscr.2018.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Sigmoid gallstone ileus: A case report and literature review in Japan

Abstract: HighlightsWe present a unique case of gallstone ileus with inguinal hernia.A one-stage operation can be considered for patients with gallstone ileus associated with cholecystocolonic fistula.A review of the literature pertaining to colonic gallstone ileus is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 4 publications
0
19
0
1
Order By: Relevance
“…This was recognised radiologically and is referred eponymously as Rigler's triad [11]. Approximately 75% of these fistulae are cholecystoduodenal, whereas only 10% to 20% are cholecystocolonic [12]. Approximately 40% to 50% of patients eventually diagnosed with gallstone ileus have a history of recent bouts of biliary colic, jaundice or acute cholecystitis [9].…”
Section: Discussionmentioning
confidence: 99%
“…This was recognised radiologically and is referred eponymously as Rigler's triad [11]. Approximately 75% of these fistulae are cholecystoduodenal, whereas only 10% to 20% are cholecystocolonic [12]. Approximately 40% to 50% of patients eventually diagnosed with gallstone ileus have a history of recent bouts of biliary colic, jaundice or acute cholecystitis [9].…”
Section: Discussionmentioning
confidence: 99%
“…Other factors that contribute to gallstone ileus are a long history of cholelithiasis, repeated episodes of acute cholecystitis and stones greater than 2 cm. According to the literature, approximately 40–50% of patients eventually diagnosed with gallstone ileus have a history of recent bouts of biliary colic, jaundice or acute cholecystitis [1, 2].…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, cholecystocolonic fistula is the most common predicted route. A previous report provided evidence-based recommendation for one-stage surgery in cases of gallstone ileus accompanied by cholecystocolonic fistula 4. This is supported by the lower natural closure rate of 10% for cholecystocolonic fistula versus the other types of cholecystointestinal fistula and the high risk of retrograde cholecystitis due to reverse flow of faecal fluid from the cholecystocolonic fistula 34…”
Section: Treatmentmentioning
confidence: 94%
“…For cases with impaction of the colon, selection of non-surgical treatment may be indicated, but 74% of cases with non-surgical treatment show failure 14. One review4 indicated that if surgery is selected, one-stage surgery is performed in majority of the cases. The sigmoid colon is the most common impaction site, mainly due to presence of intestinal stenosis caused by diverticulitis.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation